2020
DOI: 10.1177/2192568219897598
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Anticoagulation Management in Spine Surgery: Initial Findings From the AO Spine Anticoagulation Global Survey

Abstract: Study Design: Cross-sectional, international survey. Objectives: This study addressed the global perspectives concerning perioperative use of pharmacologic thromboprophylaxis during spine surgery along with its risks and benefits. Methods: A questionnaire was designed and implemented by expert members in the AO Spine community. The survey was distributed to AO Spine’s spine surgeon members (N = 3805). Data included surgeon demographic information, type and region of practice, anticoagulation principles, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Additionally, the lack of a global perspective in the NASS guidelines weaken their generalizability. In the preliminary findings from our survey data, Louie and colleagues 22 reported that only 14% of respondents described following hospital, national, or other unspecified guidelines when deciding on the use of anticoagulation. Despite this notion by our survey respondents, the AOSpine group has released thromboprophylaxis guidelines for patients suffering from spinal cord injury, which is the highest risk group for VTE in patients undergoing spine surgery.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Additionally, the lack of a global perspective in the NASS guidelines weaken their generalizability. In the preliminary findings from our survey data, Louie and colleagues 22 reported that only 14% of respondents described following hospital, national, or other unspecified guidelines when deciding on the use of anticoagulation. Despite this notion by our survey respondents, the AOSpine group has released thromboprophylaxis guidelines for patients suffering from spinal cord injury, which is the highest risk group for VTE in patients undergoing spine surgery.…”
Section: Discussionmentioning
confidence: 70%
“…12 Given the growing need for consensus surrounding recommendations regarding perioperative anticoagulation management in spine surgery, we conducted a global survey of spine surgeons within the AOSpine network to gauge their knowledge, attitudes and practices on this topic. Our preliminary findings have been reported by Louie et al 22 With that serving as a foundation, the specific focus of this study was to identify factors that contribute to the decision making of the initiation of anticoagulation after spine surgery among a global group of spine surgeons. We hypothesized that the survey responses will show heterogeneity in anticoagulation start times, with few instances of consensus of important patient or surgical factors influencing initiation decisionmaking.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The survey received a 7% response rate, and although low, this is consistent with past surveys that have been conducted and published using the AO Spine community. 15,16 In addition, we believe the data are representative as not all AO Spine members are researchers, and the proportion of respondents from each region is similar to that of the AO Spine community. While there was a respectable number of respondents that participated in the survey, not all participants completed all questions.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 94%